2022
DOI: 10.3390/e24111672
|View full text |Cite
|
Sign up to set email alerts
|

A New Exergy Disaggregation Approach for Complexity Reduction and Dissipative Equipment Isolation in Thermoeconomics

Abstract: Thermoeconomics connects thermodynamic and economic concepts in order to provide information not available in conventional energy and economic analysis. Most thermoeconomicists agree that exergy is the most appropriate thermodynamic magnitude to associate with cost. In some applications, exergy disaggregation is required. Despite the improvement in result accuracy, the modeling complexity increases. In recent years, different exergy disaggregation approaches have been proposed, mostly to deal with dissipative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The A&F Model [9] is a recent thermoeconomic approach, it was developed with the premise of reducing the complexity and computational efforts compared to other methodologies that are capable of isolating (defining input and output) dissipative equipment, such as a valve. This model also uses the physical exergy disaggregation and the definition of its terms are Helmholtz energy E A and flow work E F .…”
Section: Aandf Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The A&F Model [9] is a recent thermoeconomic approach, it was developed with the premise of reducing the complexity and computational efforts compared to other methodologies that are capable of isolating (defining input and output) dissipative equipment, such as a valve. This model also uses the physical exergy disaggregation and the definition of its terms are Helmholtz energy E A and flow work E F .…”
Section: Aandf Modelmentioning
confidence: 99%
“…Nevertheless, there is a consequent increase in the complexity of thermoeconomic modeling [5]. In this paper, five thermoeconomic models are studied: E, E T & E M [6], H&S [7], UFS [8] and the recent A&F Model [9]. The plant chosen for the analysis allows the approach of a very latent theme in thermoeconomics which is the waste cost allocation.…”
Section: Introductionmentioning
confidence: 99%
“…The diagram depicted in Figure 8 showcases the use of the A&F Model [22] in the heat pump system for the isolation of valves and the determination of their products and fuels via the utilization of Helmholtz energy (E A ) and flow work (E F ) terms.…”
Section: Aandf Modelmentioning
confidence: 99%
“…However, it can incur a loss in the accuracy of the results. Finally, the latest thermoeconomic methodology presented in the literature is the A&F model [22], a methodology proposed to isolate dissipative components with less modelling complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, when considering the cost of acquiring environmental control/treatment equipment, this model would need to depict such equipment in the physical and productive diagrams to facilitate appropriate cost allocation. However, these devices are dissipative, and several studies [32][33][34] have already demonstrated that Model E is not adequate for isolating them within the productive structure and thus analyzing them in a separate and appropriate manner.…”
mentioning
confidence: 99%